Research and Development of Environmental Monitoring Alarm and Automatic Flag Control System for Barracks - Ming-Sen Hu; Wei-Kuo Soong; Pei-Hua Tan (International Journal of Engineering and Technology Innovation, 2023)
This paper proposes a real-time flag alarm system that can monitor air quality and automatically plant colored flags to inform the people in the barracks. This system automatically measures the local PM 2.5 concentrations with PM sensors; and automatically measures the temperature and humidity with temperature and humidity sensors, then converts the measured values into the grades of danger coefficients and the grades of AQI to plant or replace flags by automatic control. The danger coefficient grades are represented by four colored flags, namely, green, blue, yellow, and red; meanwhile, the AQI grades are represented by six colored flags, namely, green, yellow, orange, red, purple, and maroon. Moreover, this system displays all measured data and related information with electronic billboards to provide a reference for people participating in outdoor activities.